1993
DOI: 10.3109/02688699309023809
|View full text |Cite
|
Sign up to set email alerts
|

The Westmead Head Injury Project outcome in severe head injury. A comparative analysis of pre-hospital, clinical and CT variables

Abstract: A prospective study of 315 consecutive patients with a severe head injury was undertaken to study factors contributing to mortality and morbidity, both in the pre-hospital and hospital phases. Entry criteria were a Glasgow Coma Scale (GCS) score of 8 or less after non-surgical resuscitation within 6 h of the injury, or a deterioration to that level within 48 h. Patients with gunshot wounds or who were dead on arrival were excluded. End points of the study were either death or at 6 months after the injury. Pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
155
3
12

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(173 citation statements)
references
References 27 publications
3
155
3
12
Order By: Relevance
“…Studies of adults have linked early hypotension following TBI with poor outcome (2,(16)(17)(18). Hypotension occurring at any point from the time of injury through resuscitation has been shown to double the mortality rate (2).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of adults have linked early hypotension following TBI with poor outcome (2,(16)(17)(18). Hypotension occurring at any point from the time of injury through resuscitation has been shown to double the mortality rate (2).…”
Section: Discussionmentioning
confidence: 99%
“…1 Prior studies have demonstrated that secondary brain insults (SBIs), such as fever, hypotension, or hypoxia, worsen outcome in patients with traumatic brain injury (TBI). [2][3][4][5][6][7][8] A retrospective study utilizing the Traumatic Coma Data Bank convincingly showed that hypotension or hypoxia at the time of hospital admission had a significant negative effect on six-month functional outcome as measured by the Glasgow Outcome Scale (GOS). 9 These events are common, as hypotension (defined in these settings as a systolic blood pressure ,90 mm Hg) is seen in up to 35% of patients with head injury.…”
mentioning
confidence: 99%
“…A study of Fearnside et al reported that 65% of patients with 3 GCS score and 10% of patients with 7-13 GCS score ended with mortality (12). In our study, while GCS levels of patients in admission decreased, the rate of surgical operations (severe: 6.1%, modarate: 25%, mild: 25%) and the rate of recovery with sequelae increased (mild: 6.1%, moderate: 0% and severe: 50%).…”
Section: Discussionmentioning
confidence: 48%